DETERMINATION OF THE PRODUCTIVITY AND CROP YIELD OF SALINE SOILS ON THE BASIS OF ADVANCED TECHNOLOGIES AND THE DEVELOPMENT OF AGROTECHNOLOGY OF THE APPLICATION OF FERTILIZERS IN OPTIMAL QUANTITIES - N. X. Hakimova; M. F. G’aybulloyeva (Web of Journals Publishing, 2025)
Salinization of soils remains one of the major threats to global agricultural productivity, especially in arid and semi-arid regions. This article explores the assessment of productivity and crop yield potential on saline soils by integrating advanced technologies, such as remote sensing, precision agriculture, and soil mapping. Additionally, the paper presents the development of agrotechnology focusing on the optimized application of fertilizers tailored to saline conditions. The results highlight that technological intervention and calculated fertilizer management can significantly enhance crop yields and rehabilitate saline soils.
Keywords: Saline soils, productivity, crop yield, advanced technologies, agrotechnology, fertilizer optimization, soil salinity management, sustainable agriculture.